Investors’ distraction and strategic repricing decisions - Navone, Marco (Journal of Banking & Finance, 2012)
In this paper I analyze investors’ reactions to changes in the expense ratios of equity mutual funds. I show that investment flows’ response to fees cannot be fully explained by looking at investors’ performance sensitivity. While performance sensitivity monotonically increases with past performance, price sensitivity does not: investors who buy top past performers seem to be “distracted” by the fund’s previous return and pay relatively little attention to the expense ratios. Moreover price sensitivity increases with fund visibility while performance sensitivity decreases, and while looking at data from 1986 to 2006 no discernible trend can be observed in the average performance sensitivity, price sensitivity strongly increases due to the dramatic increase in the availability of mutual funds’ information for retail investors. Finally I show that investment companies strategically time their repricing decisions in order to exploit time variations in price and performance sensitivities, and that fund governance quality affects the degree to which investment companies engage in this opportunistic behavior.